Sedentary Lifestyle and Academic Stress as Risk Factors for Health Disorders in Young Adults: Implications for Health Education and Prevention - Karol, Michał; Koseska, Kamila; Borowicz, Jan; Górecki, Bartosz; Kloch, Kinga; Romaniuk, Patryk; Lohin, Mariia-Khrystyna; Strawińska, Aleksandra; Bednarczyk, Małgorzata (Journal of Education, Health and Sport, 2026)
Introduction and purpose. Young adults—especially students—are increasingly exposed to the combined impact of a sedentary lifestyle and chronic academic stress. Screen-based learning and computer-mediated work promote prolonged sitting, while high academic demands limit time and energy for recovery and movement. The aim of this narrative review is to summarize current knowledge on links between sedentary behaviour, academic stress and health in young adults, and to indicate implications for health education and prevention at universities. Description of the state of knowledge. Studies show that sedentary behaviour in this age group is associated with musculoskeletal pain, early metabolic disturbances, poorer sleep and reduced psychological well-being, whereas academic stress correlates with anxiety and depressive symptoms, sleep problems, risky health behaviours and burnout. Both factors share biological and psychosocial mechanisms, including dysregulation of the stress axis and consolidation of passive, screen-based coping. The academic environment—through timetables, assessment methods and access to sports infrastructure—shapes students’ movement patterns and stress load. Interventions that combine promotion of everyday physical activity with training in stress self-regulation and sleep hygiene, supported by environmental changes that facilitate movement breaks, appear promising but are still evaluated mainly in cross-sectional or short-term studies. Summary (conclusions). Sedentary lifestyle and academic stress form a mutually reinforcing cluster of risk factors that may contribute to early health problems in young adults, supporting the need for integrated, university-based programmes that address both daily movement patterns and stress management skills.